Rapid Passenger Transport in North America in 21st Century - Tietze, Wolf (Promet - Traffic&Transportation, 2012)
The occurrence of outstanding transport innovations maylead to monumental reconstruction in large urbanised regionssuch as North America. The decisive factor in this is the introductionofTransrapid, a new rapid transport technology basedon the principle of magnetic levitation (Maglev).This paper uses the urban network of North America Eastof the 1 O(Jh meridian, together with the smaller region of California,to demonstrate the advantages of innovative transporttechnology as the optimal link between road and air transport.Despite requiring less energy input, achieving better adaptationto the topography of the country, causing less noise and beingsubject to less wear and tear, Transrapid achieves almost twicethe speed of conventional trains.